Reusable bags: an alternative to reduce the impact of large scale caused by the elimination of irregular disposable bags - Rizzatti, Cláudia Bach; Lorenzett, Juliana Benitti; Lorenzett, Daniel Benitti; Godoy, Leoni Pentiado (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
This study aimed to determine the receptivity and acceptance of customers in a supermarket chain in relation to the adoption of reusable bags as a strategy for environmental marketing. Therefore, we conducted a case study by implementing a structured questionnaire. The questionnaire was administered to a non-probability sample of 150 customers of a supermarket chain, located in the town of Santa Maria, RS. The results were positive regarding customer acceptance of replacement of disposable bags for reusable bags, however, despite the acceptance is high, adherence is still low, since most customers forget to take reusable bags when they go shopping. This result demonstrates the need to increase investments in environmental education, to raise awareness about the need and importance of protecting and preserving the environment.